TENANT PLACEMENT STRATEGY WITHIN A MALL IN JAKARTA - Juana Judith Huliselan; Trisa Pramudita (DeReMa (Development Research of Management): Jurnal Manajemen, 2020)
Jakarta is the city that has the largest amount of shopping centers in the world and has been named “The Capital City of the World’s Shopping Center”. The high competition has become a challenge for the mall’s manager to choose the right tenant placement strategy in order to increase the profits of both tenants and the mall’s management. Broadly, the tenant placement strategy could be divided into two core strategies, dispersion strategy and departmentalization strategy. This research argues that the tenant placement strategy is affected by the height of the mall and mall’s configuration. The research’s purpose is to analyze the influence of the variables such as total levels, levels, level gross leaseable area, total units, units, complexity, net leasable area ratio, and total gross leasable area on the degree of departmentalization. The research subject is the mall’s floor of a mall located in Jakarta in the business district that not only has four floor levels or more but also has a total gross leasable area of more than 100,000 m2. Based on these criteria and using judgmental sampling technique, there were 51 observations that included in the research. The data that used are the result of the ArcGis analysis which is then processed by statistic software called eViews. The result of the research shows that the tenant placement strategy is affected by the configuration of the mall as a whole, not by the floor level of the mall individually. The degree of departmentalization is affected positively by the total gross leasable area of the mall. This finding could be used as the suggestion for the mall’s management to increase the mall’s productivity by choosing the right tenant placement strategy in order to increase the profits of both tenants and the mall’s management.Abstrak Bahasa Indonesia Jakarta adalah kota yang memiliki jumlah pusat perbelanjaan terbesar di dunia dan telah dinamai "Ibukota Pusat Perbelanjaan Dunia". Persaingan yang tinggi telah menjadi tantangan bagi manajer mal untuk memilih strategi penempatan penyewa yang tepat untuk meningkatkan keuntungan penyewa dan manajemen mal. Secara umum, strategi penempatan penyewa dapat dibagi menjadi dua strategi inti, strategi dispersi dan strategi departemen. Penelitian ini berpendapat bahwa strategi penempatan penyewa dipengaruhi oleh ketinggian mal dan konfigurasi mal. Tujuan penelitian ini adalah untuk menganalisis pengaruh variabel seperti level total, level, gross leasable area, total unit, unit, kompleksitas, rasio net keasable area, dan total luas leasable bruto pada tingkat departemen. Subjek penelitian adalah lantai mal di mal yang berlokasi di Jakarta yang berlokasi di sekitar kawasan bisnis yang tidak hanya memiliki empat lantai atau lebih, tetapi juga memiliki total gross leasable area lebih dari 100.000 m2. Berdasarkan kriteria ini dan menggunakan teknik judgemental sampling, ada 51 pengamatan yang termasuk dalam penelitian. Data yang digunakan adalah hasil analisis ArcGis yang kemudian diproses dengan menggunakan eViews. Hasil penelitian menunjukkan bahwa strategi penempatan penyewa dipengaruhi oleh konfigurasi mal secara keseluruhan, bukan oleh tingkat lantai mal secara individual. Tingkat departemenisasi dipengaruhi secara positif oleh total gross leasable area. Temuan ini dapat digunakan sebagai saran bagi manajemen mal untuk meningkatkan produktivitas mal dengan memilih strategi penempatan penyewa yang tepat untuk meningkatkan keuntungan penyewa dan manajemen mal.